Preparation and application of super-hydrophilic difunctional electrocatalyst with built-in electric field

By tightly coupling NiTe2 and MoTe2 on the conductive current collector substrate, a built-in electric field was constructed, and a super hydrophilic NiTe2/MoTe2 dual-function catalyst was prepared, which solved the problem of insufficient electrocatalytic activity of the existing telluride catalyst, and achieved efficient sulfur oxidation reaction and hydrogen evolution reaction.

CN119710800AActive Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411866762.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing telluride catalysts have insufficient electrocatalytic activity in sulfur oxidation reaction and hydrogen evolution reaction, and traditional synthesis methods lead to easy accumulation of catalyst particles and cover active sites, making it difficult to maximize utilization.

Method used

By tightly coupling NiTe2 and MoTe2 on the conductive current collector substrate, a built-in electric field is constructed to increase the charge density of the active site, and a super hydrophilic NiTe2/MoTe2 bifunctional catalyst is prepared.

Benefits of technology

It achieves catalytic activity with excellent conductivity and low reaction overpotential, improves the rate and activity of electrocatalytic reactions, and the catalyst has super hydrophilic characteristics, which promotes rapid contact and diffusion of electrolytes and gas products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses preparation and application of a super-hydrophilic bifunctional electrocatalyst with a built-in electric field, relates to the technical field of preparation of energy-saving hydrogen production electrocatalysts, and comprises pretreatment of a conductive current collector substrate, hydrothermal synthesis of a NiMoO4 precursor, hydrothermal synthesis of NiTe2 / MoTe2, and energy-saving hydrogen production application of SOR-assisted electrolyzed water. By utilizing a built-in electric field strategy, an electron transfer path of a catalyst is effectively enhanced by in-situ self-growth of an active substance on a conductive current collector substrate, sufficient infiltration of an active site and an electrolyte is promoted, effective utilization of an electro-catalytic reaction site is improved, and the catalytic efficiency is improved. The telluride is applied to the sulfur ion oxidation reaction assisted water electrolysis energy-saving hydrogen production technology, compared with a traditional all-water decomposition hydrogen production technology, energy consumption is reduced, development of a green chemical technology can be promoted, important support is provided for energy transformation and clean energy production, and the method has a wide application prospect. The huge potential in the aspects of meeting the time policy and promoting the sustainable development target is manifested.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and particularly relates to the preparation and application of a superhydrophilic bifunctional electrocatalyst with an internal electric field. Background Art

[0002] The organic combination of small molecule electrochemical oxidation reaction and electrolytic water hydrogen production technology has opened up a forward-looking and feasible path for the energy-saving development of renewable energy. Nowadays, a large amount of sulfide pollutant resources are contained in domestic sewage and industrial wastewater, with an annual discharge exceeding 60 million tons. This abundant sulfide resource provides an ideal raw material basis for large-scale hydrogen production. The electrochemical sulfide oxidation reaction (SOR) technology can not only efficiently purify these environmental pollutants, but also convert them into high-value-added products, thus realizing the efficient utilization of waste resources and the simplification of the treatment process. More importantly, the sulfide ion oxidation reaction is a two-electron reaction, which has a lower redox potential than the oxygen evolution reaction (OER) in traditional electrolytic water hydrogen production, endowing it with significant advantages and great potential in the coupled technology of electrochemical desulfurization and energy-saving hydrogen production, and injecting new impetus into the sustainable development of the energy industry.

[0003] In past studies, researchers have always been committed to exploring and developing efficient and stable non-precious metal catalysts in order to achieve breakthrough progress in the field of catalysis. Among them, due to telluride having a lower electronegativity (Te < Se < S < O) and better band alignment, it exhibits the highest electronic conductivity (up to 1×10 at 300K) -5S / m) and stronger metallic properties and excellent electron transfer rate in electrocatalytic reactions. However, the electrocatalytic performance of single-phase TMT is unsatisfactory, and it needs to be modified and optimized to improve its electrocatalytic activity. For example, Zhang et al. prepared cobalt-based tellurides with good electronic conductivity by co-doping Ni and Fe, and electronically modified TMT through doping engineering to improve its electrochemical oxidation activity, but its hydrogen evolution activity still needs to be further improved to achieve efficient hydrogen production (DOI: 10.1039 / d4ta01929f). Wu et al. designed a one-dimensional NiFeCo-OH / NiTe nanorod array with an amorphous / crystalline interface through defect engineering, and improved the electrocatalytic activity through defect design, but traditional electrochemical synthesis makes the catalyst particles easy to accumulate and deposit unevenly, making it difficult to expose the active sites to the greatest extent (DOI: 10.1039 / d4ta00772g). Kim et al. designed a MOF structure to assist in the synthesis of porous CoTe2 / MnTe2, enhancing the inherent electrochemical surface area and charge transfer of the material to achieve improved electrocatalytic activity, but this method requires the catalyst material to have excellent affinity for the electrolyte in order to achieve effective utilization of active sites (DOI: 10.1039 / d4ta01929f). It can be seen that the design and synthesis of existing telluride catalysts have the following problems: (1) There is relatively little research on tellurides. The electrocatalytic activity of a single component telluride is insufficient, and the high overpotential in the sulfur oxidation reaction and hydrogen evolution reaction makes it difficult to achieve energy-saving desulfurization and hydrogen production. (2) In the synthesis of traditional tellurides, there are problems of catalyst particle clustering and the electrocatalytic active sites being covered, making it difficult to maximize the utilization of the electrochemically active surface area; (3) In electrochemical reactions involving gas participation, it is difficult for the catalyst and the electrolyte to achieve rapid contact, and the gas products are difficult to diffuse quickly, resulting in low utilization of active sites on the catalyst surface. Summary of the invention

[0004] In order to solve the above technical problems, the present invention uses a rough three-dimensional porous nickel foam NF as a conductive current collector substrate to effectively increase the electrocatalytic active surface area of ​​the catalyst. NiTe2 and MoTe2 are tightly coupled by a hydrothermal method, and a built-in electric field between the two phase components is constructed by the redistribution caused by the spontaneous electron flow on the heterogeneous interface. The charge density of the active site is increased by the built-in electric field strategy, and finally a super-hydrophilic NiTe2 / MoTe2 bifunctional catalyst with excellent conductivity, low reaction overpotential and catalytic activity is prepared. The technical scheme is as follows: A method for preparing a super-hydrophilic bifunctional electrocatalyst with a built-in electric field comprises the following steps: (1) Pretreatment of the conductive current collector substrate: After ultrasonic etching of the conductive current collector substrate in dilute hydrochloric acid, rinse with deionized water and anhydrous ethanol, and vacuum dry for later use; (2) Hydrothermal synthesis of NiMoO4 precursor: nickel salt and molybdenum salt are uniformly dispersed in a solvent, added to a pretreated conductive current collector substrate, and subjected to a hydrothermal reaction to obtain a NiMoO4 precursor; (3) Hydrothermal synthesis of NiTe2 / MoTe2: The reducing agent and tellurium source are uniformly dispersed in a solvent, and a NiMoO4 precursor is added to carry out a hydrothermal tellurization reaction to obtain NiTe2 / MoTe2.

[0005] As a preferred embodiment of the preparation method of the present invention, the conductive current collector substrate in step (1) is one or more of foamed nickel, foamed iron, foamed copper, and foamed molybdenum.

[0006] As a preferred embodiment of the preparation method of the present invention, the concentration of the dilute hydrochloric acid in step (1) is 2-5 M, and the etching time is 20-40 min.

[0007] In an exemplary specific embodiment of the present invention, the nickel foam is cut into a size of 1.5×1.0 cm, and ultrasonic etching is performed in 3 M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface; after the ultrasonic etching is completed, the nickel foam is washed multiple times with deionized water and anhydrous ethanol to ensure that the residual dilute hydrochloric acid is completely removed; finally, the treated nickel foam is dried under vacuum conditions at 60°C to completely remove moisture and prevent oxidation, so as to prepare for subsequent use.

[0008] As a preferred embodiment of the preparation method of the present invention, the nickel salt in step (2) is one or more of nickel nitrate, nickel chloride, and nickel sulfate, preferably nickel nitrate; the molybdenum salt is one or more of ammonium molybdate and sodium molybdate, preferably ammonium molybdate; and the solvent is one or more of N,N-dimethylformamide (DMF), ethanol, and deionized water, preferably a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:5.

[0009] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the nickel salt to the molybdenum salt in step (2) is 1:0.5-2; preferably, the molar ratio of the nickel salt to the molybdenum salt is 1:1-2; more preferably, the molar ratio of the nickel salt to the molybdenum salt is 1:1.

[0010] As a preferred embodiment of the preparation method of the present invention, the hydrothermal reaction in step (2) is carried out in a 70 mL hydrothermal kettle, the hydrothermal temperature is 120-180° C., and the hydrothermal time is 4-7 h. Preferably, the hydrothermal temperature is 150° C. and the hydrothermal time is 6 h.

[0011] As a preferred embodiment of the preparation method of the present invention, the reducing agent in step (3) is one or more of citric acid, hydrazine hydrate, ammonia water, and NaBH4, preferably NaBH4; the tellurium source is one or more of tellurium dioxide, sodium tellurite, and tellurium powder, preferably tellurium powder. As a preferred embodiment of the preparation method of the present invention, the molar mass ratio of the tellurium source to the reducing agent in step (3) is 0.6-0.9:28-33.

[0012] As a preferred embodiment of the preparation method of the present invention, the hydrothermal reaction in step (3) is carried out in a 70 mL hydrothermal kettle, the hydrothermal temperature is 120-180° C., and the hydrothermal time is 10-15 h; preferably, the hydrothermal reaction temperature is 160° C. and the reaction time is 12 h.

[0013] Another object of the present invention is to overcome the deficiencies in the prior art and provide a super-hydrophilic bifunctional electrocatalyst with a built-in electric field prepared by the above-mentioned preparation method. The composite material has super-hydrophilic properties and there is a built-in electric field effect between the two-phase heterogeneous components.

[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide the application of the above-mentioned super-hydrophilic bifunctional electrocatalyst with a built-in electric field in electrocatalytic sulfur ion oxidation coupled with water electrolysis to produce hydrogen.

[0015] (1) Unique built-in electric field strategy: Through electron rearrangement at the heterogeneous interface, interface polarization is caused and a potential difference is generated. Electrons move until the Fermi level is aligned, forming electron-rich and electron-deficient regions and establishing a built-in electric field. This built-in electric field can increase the charge density of active sites, improve intrinsic activity, and increase the reaction concentration at the interface, thereby increasing the reaction rate and overall reaction activity.

[0016] (2) Super-hydrophilic property: NiTe2 / MoTe2 loaded on the conductive current collector substrate has super-strong hydrophilicity. On the one hand, its hydrophilicity helps to quickly contact with the electrolyte. On the other hand, the surface affinity for liquid water will inherently reduce the material's adhesion to bubbles, thereby allowing the rapid release of gas products. The two synergistically promote the mass transfer and electron transfer of the electrocatalytic reaction, thereby enhancing its electrocatalytic activity.

[0017] (3) In-situ self-growth strategy based on porous conductive current collector nickel foam: The robust anchoring and dispersion of NiTe2 / MoTe2 on nickel foam not only enhances the number of effective loading and active sites, but also circumvents polymer binders and conductive additives. In addition, the strong adhesion and high integration between NiTe2 / MoTe2 and the conductive substrate nickel foam ensure stability under continuous high current density electrocatalysis.

[0018] (4) NiTe2 / MoTe2 as a bifunctional electrocatalyst has realized the application of telluride in the sulfur ion oxidation reaction to assist the energy-saving hydrogen production technology of water electrolysis, which saves nearly 63% of energy consumption compared with the traditional full water decomposition hydrogen production technology. This application can not only promote the development of green chemical technology, but also provide important support for energy transformation and clean energy production, demonstrating its great potential in meeting the policies of the times and promoting sustainable development goals. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 is the XRD diagram of NiTe2 / MoTe2 in the embodiment of the present invention; Figure 2 This is a picture of the water contact angle of NiTe2 / MoTe2 in an embodiment of the present invention; Figure 3 The LSV curves of electrochemical SOR and HER of the materials prepared in the embodiments of the present invention are shown in FIG. 1 , wherein (a) is the LSV curve of SOR, and (b) is the LSV curve of HER; Figure 4 The electrochemically active surface area ECSA diagram in the embodiment of the present invention; Figure 5 The impedance diagram of NiTe2 / MoTe2 and NiMoO4 in the embodiment of the present invention; Figure 6 LSV curves of SOR / / HER and OER / / HER coupled systems based on NiTe2 / MoTe2 electrodes. DETAILED DESCRIPTION

[0020] In order to more clearly demonstrate the purpose, features and advantages of the present invention, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0021] In the following description, a large number of specific details are provided to help fully understand the present invention. However, the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the core concept of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0022] In addition, the "one embodiment" or "embodiment" mentioned herein refers to a specific feature, structure or characteristic included in at least one implementation of the present invention. The "in one embodiment" appearing in different parts of this specification does not necessarily refer to the same embodiment, nor is it an independent or selective embodiment that is mutually exclusive with other embodiments.

[0023] The nickel foam in the embodiment of the present invention was purchased from Hefei Kejing Material Technology Co., Ltd., with specifications of: length 1000mm*width 300mm*thickness 1.6mm, 3N surface density 350g / m 2 ; Other raw materials are common commercially available products.

[0024] The present invention uses an X-ray diffractometer and a Chenhua 660e electrochemical workstation to characterize and analyze the comparative material prepared in this embodiment.

[0025] In the embodiment of the present invention, the SOR and HER performance tests under the three-electrode system are as follows: (1) Electrochemical performance test of SOR: The test was carried out on a CHI 660E electrochemical workstation using a traditional three-electrode system. The synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The electrolyte was 1.00 M NaOH + 1.00 M Na2S. The SOR electrochemical performance was tested in the range of -0.2 ~ -1.0 V (relative to Ag / AgCl) at 5 mV·s -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and the final LSV curve was obtained through 90% impedance compensation.

[0026] (2) HER electrochemical performance test: The test was also carried out on a CHI 660E electrochemical workstation, using a traditional three-electrode system. The synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrolyte was 1.00 M NaOH. In the range of 1.0 ~ 1.6 V (relative to Ag / AgCl), the HER electrochemical performance was measured at 5 mV·s -1 The LSV curve was tested at a scan rate of , and the final LSV curve was obtained through 90% impedance compensation.

[0027] In the embodiment of the present invention, the electrochemically active surface area (ECSA) of the catalyst is tested as follows: The test was carried out on a CHI 660E electrochemical workstation using a traditional three-electrode system. The synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrolyte was 1.00 M NaOH and 1.00 M NaOH + 1.00 M Na2S. -1, 40 mV·s -1 , 60 mV·s -1 , 80 mV·s -1 , 100 mV·s -1 ), the CV curve test was carried out under the condition of dl ) is closely related to ECSA, which can be obtained by plotting the charge current difference ∆j = (j a -j c ) to estimate, where the linear slope fit C dl is twice the scanning rate. Therefore, C dl It can be approximately expressed by the following formula.

[0028] j=S×C dl ×ν Where j is half of the double layer capacitance current density (mA cm -2 ), S is the measured area of ​​the electrode (S = 1.0 × 1.0 cm 2 ), ν is the scanning rate (mV·S -1 ).

[0029] In the embodiment of the present invention, the performance test of the two-electrode SOR / / HER and OER / / HER coupling system is as follows: (1) Assembly and testing of SOR / / HER: The test was carried out on a CHI 660E electrochemical workstation. The prepared catalyst was used as the working electrode for both the cathode and the anode. The cathode electrolyte was 1.00 M NaOH and the anode electrolyte was 1.00 M NaOH + 1.00 M Na2S. The SOR / / HER was charged at 5 mV·s in the range of 0 to 0.8 V (vs. Ag / AgCl). -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and the final LSV curve was obtained through 90% impedance compensation.

[0030] (2) Assembly and testing of OER / / HER: The test was carried out on a CHI 660E electrochemical workstation, with the prepared catalyst as the working electrode, the platinum electrode as the counter electrode, and 1.00 M NaOH as the cathode and anode electrolytes. The linear sweep voltammetry (LSV) curve was tested in the range of 1.2 to 2.0 V (relative to Ag / AgCl) at a scan rate of 5 mV·s-1, and the final LSV curve was obtained by 90% impedance compensation. Example 1

[0031] Synthesize NiTe2 / MoTe2 as follows: (1) Pretreatment of the conductive current collector substrate: First, the nickel foam was cut into a size of 1.5 × 1.0 cm; Then, the cut nickel foam was placed in 3 M dilute hydrochloric acid and ultrasonically etched for 30 minutes to remove the oxide layer on the surface; After ultrasonic etching, the nickel foam was washed several times with deionized water and anhydrous ethanol to ensure that the residual dilute hydrochloric acid was completely removed; Finally, the treated nickel foam is dried under vacuum conditions at 60°C to completely remove moisture and prevent oxidation, preparing for subsequent use.

[0032] (2) Hydrothermal synthesis of NiMoO4 precursor: Accurately weigh 0.3 mmol nickel nitrate and 0.3 mmol ammonium molybdate tetrahydrate, evenly disperse them in 15 mL deionized water, stir for 30 min, add 3 mL anhydrous ethanol, and continue stirring for 15 min to obtain a uniform mixed solution; The conductive substrate pretreated in step (1) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 150° C. for 6 h. After the reaction was naturally cooled to room temperature, the sample was carefully taken out, and the sample was repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven at 60°C for drying to obtain a NiMoO4 precursor.

[0033] (3) Hydrothermal synthesis of NiTe2 / MoTe2: Accurately weigh 31 mmol NaBH4 and add it to 18 mL deionized water. Stir for 15 min until dissolved. Then accurately weigh 0.8 mmol tellurium powder and add it to the mixed solution. Stir for 3 h to obtain a purple uniform solution. The precursor obtained in step (2) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 160°C and a reaction time of 12 h. After the reaction was cooled naturally to room temperature, the sample was carefully taken out and repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven and dried at 60°C to obtain NiTe2 / MoTe2.

[0034] Depend on Figure 1 It can be seen that the samples NiTe2 / MoTe2, NiTe2, MoTe2 and NiMoO4 correspond well to the standard card, indicating the successful synthesis of the samples in the embodiment. Figure 2It can be seen from the water contact angle that the NiTe2 / MoTe2 synthesized in the example has superhydrophilic properties. Based on the energy balance principle of the solid-liquid-gas three-phase interface, the surface affinity for liquid water will inherently reduce the material's adhesion to bubbles. Therefore, the superhydrophilic NiTe2 / MoTe2 catalyst not only facilitates rapid contact with the electrolyte in the electrochemical reaction, but also facilitates the rapid release of gas products, which is crucial for catalytic reactions involving gas generation. Example 2

[0035] Synthesize NiTe2 as follows: (1) Pretreatment of the conductive current collector substrate: same as in Example 1.

[0036] (2) Hydrothermal synthesis of NiO precursor: Accurately weigh 0.3 mmol nickel nitrate and evenly disperse it in 15 mL deionized water. After stirring for 30 min, add 3 mL of anhydrous ethanol and continue stirring for 15 min to obtain a uniform mixed solution. The conductive substrate pretreated in step (1) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 150° C. for 6 h. After the reaction was cooled naturally to room temperature, the sample was carefully taken out, and the sample was repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven at 60° C. for drying to obtain a NiO precursor.

[0037] (3) Hydrothermal synthesis of NiTe2: Accurately weigh 31 mmol NaBH4 and add it to 18 mL deionized water. Stir for 15 min until dissolved. Then accurately weigh 0.8 mmol tellurium powder and add it to the mixed solution. Stir for 3 h to obtain a purple uniform solution. The precursor obtained in step (2) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 160°C and a reaction time of 12 h. After the reaction was cooled naturally to room temperature, the sample was carefully taken out and repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven and dried at 60°C to obtain NiTe2. Example 3

[0038] MoTe2 was synthesized as follows: (1) Pretreatment of the conductive current collector substrate: same as in Example 1.

[0039] (2) Hydrothermal synthesis of MoO3 precursor: Accurately weigh 0.3 mmol of ammonium molybdate tetrahydrate and evenly disperse it in 15 mL of deionized water. After stirring for 30 min, add 3 mL of anhydrous ethanol and continue stirring for 15 min to obtain a uniform mixed solution. The conductive substrate pretreated in step (1) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 150° C. for 6 h. After the reaction was cooled naturally to room temperature, the sample was carefully taken out and repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven and dried at 60°C to obtain a MoO3 precursor.

[0040] (3) Hydrothermal synthesis of MoTe2: Accurately weigh 31 mmol NaBH4 and add it to 18 mL deionized water. Stir for 15 min until dissolved. Then accurately weigh 0.8 mmol tellurium powder and add it to the mixed solution. Stir for 3 h to obtain a purple uniform solution. The precursor obtained in step (2) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 160°C and a reaction time of 12 h. After the reaction was cooled naturally to room temperature, the sample was carefully taken out and repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven at 60°C for drying to obtain MoTe2. Example 4

[0041] Synthesize NiMoO4 by the following steps: (1) Pretreatment of the conductive current collector substrate: same as in Example 1.

[0042] (2) Hydrothermal synthesis of NiMoO4: Accurately weigh 0.3 mmol nickel nitrate and 0.3 mmol ammonium molybdate tetrahydrate, evenly disperse them in 15 mL deionized water, stir for 30 min, add 3 mL anhydrous ethanol, and continue stirring for 15 min to obtain a uniform mixed solution; The conductive substrate pretreated in step (1) and the mixed solution were transferred to a reactor for hydrothermal reaction at a temperature of 150° C. for 6 h. After the reaction was naturally cooled to room temperature, the sample was carefully taken out, and the sample was repeatedly rinsed with deionized water and anhydrous ethanol, respectively. The rinsed sample was placed in a vacuum oven at 60°C for drying to obtain a NiMoO4 precursor. Example 5

[0043] The NiTe2 / MoTe2-2 / 3 with Ni:Mo ratio of 2:3 was synthesized as follows: (1) Pretreatment of the conductive current collector substrate: same as in Example 1.

[0044] (2) Hydrothermal synthesis of NiMoO4-2 / 3 precursor: The difference from Example 1 is that the amount of ammonium molybdate tetrahydrate used is 0.45 mmol, and the preparation method is the same as Example 1.

[0045] (3) Hydrothermal synthesis of NiTe2 / MoTe2-2 / 3: Referring to the preparation method of Example 1, NiTe2 / MoTe2-2 / 3 was obtained. Example 6

[0046] The following steps are used to synthesize NiTe2 / MoTe2-1 / 2 with a Ni:Mo ratio of 1:2: (1) Pretreatment of the conductive current collector substrate: same as in Example 1.

[0047] (2) Hydrothermal synthesis of NiMoO4-1 / 2 precursor: The difference from Example 1 is that the amount of ammonium molybdate tetrahydrate used is 0.6 mmol, and the preparation method is the same as Example 1.

[0048] (3) Hydrothermal synthesis of NiTe2 / MoTe2-1 / 2: Referring to the preparation method of Example 1, NiTe2 / MoTe2-1 / 2 was obtained. Example 7

[0049] The following steps are used to synthesize NiTe2 / MoTe2-2 / 1 with a Ni:Mo ratio of 2:1: (1) Pretreatment of the conductive current collector substrate: same as in Example 1.

[0050] (2) Hydrothermal synthesis of NiMoO4-2 / 1 precursor: The difference from Example 1 is that the amount of ammonium molybdate tetrahydrate used is 0.15 mmol, and the preparation method is the same as Example 1.

[0051] (3) Hydrothermal synthesis of NiTe2 / MoTe2-2 / 1: Referring to the preparation method of Example 1, NiTe2 / MoTe2-2 / 1 was obtained.

[0052] Evaluation of electrocatalytic performance of three-electrode system: See the LSV curves of electrochemical SOR and HER of NiTe2 / MoTe2 and examples for details. Figure 3 .Depend on Figure 3 It can be seen that the electrocatalytic activity of NiTe2 / MoTe2 is significantly better than that of NiTe2 and MoTe2, and only 0.32 V and 0.15 V overpotential are required to reach 100 mA cm in SOR and HER, respectively. -2This is attributed to the built-in electric field strategy that induces electron localization around the heterointerface, adjusts the electronic structure of the active center, and significantly reduces the reaction energy barrier of the key steps of the electrochemical reaction, thereby effectively improving the electrocatalytic activity of NiTe2 / MoTe2.

[0053] The electrocatalytic SOR and HER performance of the examples were evaluated using a 100 mA·cm -2 The overpotential at a current density of 2.5 Å was used as a measure of the catalytic activity. The specific results are shown in Table 1.

[0054] Table 1

[0055] As shown in Table 1, the HER and SOR performances of samples with different Ni:Mo are unsatisfactory. This is because different Ni:Mo have different constructions of the built-in electric field and different effects on the electron rearrangement at the heterogeneous interface, resulting in poor electron transfer rate and electrochemical activity of the samples during the electrocatalytic reaction. As shown in Table 1, reasonable regulation of the ratio of transition metal sources can optimize the electrostatic field and electron transfer at the heterogeneous interface of the sample, thereby further improving its responsiveness to the electrochemical reaction and optimizing its electrocatalytic performance.

[0056] Electrochemical intrinsic kinetics exploration: Since the electrochemical double layer capacitance (Cdl) is closely related to ECSA, the electrochemical active surface area was calculated by testing CV at different scan rates. Figure 4 It can be seen that NiTe2 / MoTe2 has the largest electrochemically active surface area (154.5 mF·cm -2 and 567.44 mF·cm -2 This is attributed to two aspects. First, the three-dimensional porous conductive current collector substrate has more electron transfer paths and a rougher surface, which effectively exposes the active sites. Second, the construction of the built-in electric field effectively exposes the electrochemical active surface area through electron rearrangement and electron transfer.

[0057] like Figure 5 The impedance diagram of the equivalent circuit fitting shows that NiTe2 / MoTe2 has a smaller interfacial resistance, indicating that it has the best electrocatalytic kinetics. In summary, the good electrocatalytic activity of NiTe2 / MoTe2 is attributed to its good electrochemical intrinsic kinetics.

[0058] Evaluation of electrocatalytic performance of two-electrode system: Depend on Figure 6 It can be obtained that the SOR\\HER system is at 100 mA·cm -2The overpotential under current density is only 0.61 V, while that of OER\\HER system is 1.67 V. The SOR\\HER system saves about 63% of energy consumption. It can be seen that the bifunctional NiTe2 / MoTe2 can be used as the cathode and anode catalyst of the SOR\\HER system at the same time, indicating that the integrated overall reaction has great prospects in environmentally friendly sulfur recovery with energy-saving H2 generation and improved electron utilization efficiency.

[0059] In summary, in view of the long-standing problems of insufficient electrocatalytic activity of tellurides and easy clustering of catalyst particles, the present invention effectively improves the electrocatalytic activity of catalysts from the following two aspects: (1) Three-dimensional porous nickel foam is used as a conductive substrate to improve the mechanical strength of the independent electrode on the one hand and significantly increase the specific surface area of ​​the catalyst on the other hand. This enhancement in turn increases the availability of active sites, promotes charge transfer, and provides diffusion channels, thereby improving the catalytic activity of the resulting material; (2) The built-in electric field strategy is adopted to promote the rearrangement of interface electrons between different components through the construction of heterogeneous structures, which is conducive to regulating the strip structure and limiting the intermediate activation barrier during the catalytic reaction; (3) The catalytic material with super-hydrophilic material properties is grown in situ to achieve rapid contact between the electrocatalytic active sites and the electrolyte, thereby promoting rapid mass transfer and electron transfer of the catalyst in the electrochemical reaction.

[0060] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a super-hydrophilic bifunctional electrocatalyst with a built-in electric field, characterized in that: The structural unit of the super-hydrophilic bifunctional electrocatalyst with a built-in electric field comprises a conductive current collector substrate, nickel telluride and molybdenum telluride in-situ grown on the substrate layer; the preparation method comprises the following steps: (1) Pretreatment of the conductive current collector substrate: After ultrasonic etching of the conductive current collector substrate in dilute hydrochloric acid, rinse with deionized water and anhydrous ethanol, and vacuum dry for later use; (2) Hydrothermal synthesis of NiMoO4 precursor: nickel salt and molybdenum salt are uniformly dispersed in a solvent, added to a pretreated conductive current collector substrate, and subjected to a hydrothermal reaction to obtain a NiMoO4 precursor; (3) Hydrothermal synthesis of NiTe2 / MoTe2: The reducing agent and tellurium source are uniformly dispersed in a solvent, and a NiMoO4 precursor is added to carry out a hydrothermal tellurization reaction to obtain NiTe2 / MoTe2.

2. The method for preparing the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 1, characterized in that: In step (1), the conductive current collector substrate is one or more of foamed nickel, foamed iron, foamed copper, and foamed molybdenum.

3. The method for preparing the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 1, characterized in that: In step (1), the concentration of dilute hydrochloric acid is 2-5 mol / L, and the etching time is 20-40 min.

4. The method for preparing the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 1, characterized in that: In step (2), the nickel salt is one or more of nickel nitrate, nickel chloride, and nickel sulfate; the molybdenum salt is one or more of ammonium molybdate and sodium molybdate; the solvent is one or more of DMF, ethanol, and deionized water; wherein the molar ratio of the nickel salt to the molybdenum salt is 1:0.5-2.

5. The method for preparing the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 1, characterized in that: The hydrothermal temperature of the hydrothermal reaction in step (2) is 120-180° C., and the hydrothermal time is 4-7 h.

6. The method for preparing the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 1, characterized in that: In step (3), the reducing agent is one or more of citric acid, hydrazine hydrate, ammonia water, and NaBH4; or one or more of tellurium dioxide, sodium tellurite, and tellurium powder; wherein the molar mass ratio of the tellurium source to the reducing agent is 0.6-0.9:28-33 mmol.

7. The method for preparing the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 1, characterized in that: The hydrothermal temperature of the hydrothermal reaction in step (3) is 120-180° C., and the hydrothermal time is 10-15 h.

8. A super-hydrophilic bifunctional electrocatalyst with a built-in electric field obtained by the method according to any one of claims 1 to 7.

9. Use of the super-hydrophilic bifunctional electrocatalyst with built-in electric field as claimed in claim 8 in hydrogen production by water electrolysis.

10. The use according to claim 9, characterized in that: The super-hydrophilic bifunctional electrocatalyst with a built-in electric field is used in electrocatalytic sulfur ion oxidation coupled with water electrolysis to produce hydrogen.

Citation Information

Patent Citations

  • Core-shell structure super-hydrophilic super-aerophobic efficient hydrogen evolution catalyst and preparation method thereof

    CN113089014A

  • Phosphorus-doped cobalt molybdate HER / SOR bifunctional catalyst, preparation method and application

    CN117845256A

  • Foamed nickel in-situ growth multistage self-assembly molybdenum ditelluride / nickel telluride nanosheet bifunctional self-supporting electrode and preparation method and application thereof

    CN117888140A

  • Preparation method for foamed nickel-based catalyst for hydrogen production by water electrolysis

    WO2021184563A1